Tangential double-enhanced gradient bone repair hydrogel material based on concentric triangular lantern ring structure and preparation method thereof

By introducing concentric triangular ring structure and HA concentration gradient into bone repair hydrogel materials, and combining it with the spatial distribution of vascular drugs, the problem of insufficient mechanical properties of traditional bone repair hydrogel materials is solved, and the mechanical enhancement of the materials is achieved and the optimization of osteogenic function significantly improves the bone repair effect.

CN119405904APending Publication Date: 2025-02-11ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411302249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional bone repair hydrogel materials have insufficient mechanical properties, which can easily lead to rupture and fracture, affecting the bone repair effect.

Method used

The tangential double-enhanced gradient bone repair hydrogel material is adopted based on the concentric triangle collar structure. By introducing the concentric triangle collar composite structure and the HA concentration gradient, it combines to promote the spatial distribution of vascular drugs to achieve the mechanical enhancement and osteogenic function of the material. optimization.

Benefits of technology

The tangential compressive/flexural strength of hydrogel materials is significantly improved, the material stability during bone repair is ensured, and the osteogenic activity is optimized through gradient structure and drug release, improving the bone repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405904A_ABST
    Figure CN119405904A_ABST
Patent Text Reader

Abstract

The invention discloses a tangential double-enhanced gradient bone repair hydrogel material based on a concentric triangular lantern ring structure and a preparation method of the tangential double-enhanced gradient bone repair hydrogel material. Comprising a base and a sleeve, the appearance of the base is circular, and a concentric triangular lantern ring type groove is formed in the inner side of the base and used for being detachably combined with the sleeve for use; (2) respectively preparing methylacryloylated sodium alginate solutions compounded with hydroxyapatite (HA) with different concentrations, and adding a blood vessel promoting drug into the HA solution with low concentration; and (3) preferentially pouring the solution with the high-concentration HA into the innermost side of a mold, carrying out UV curing and freezing demolding, then carrying out circulating pouring and curing from inside to outside according to a sequence that the concentration of the HA is decreased progressively, and finally, carrying out complete UV curing to obtain the required bone repair hydrogel material. The hydrogel material has both compression resistance and bending resistance in the tangential direction by virtue of the concentric triangular lantern ring structure, and meanwhile, shows the functions of initial blood vessel formation and complete-cycle osteogenesis promotion, so that a brand new strategy is provided for bone repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bone repair material preparation, and in particular to a tangential double-enhanced gradient bone repair hydrogel material based on a concentric triangle ring structure and a preparation method thereof. Background Art

[0002] Bone defect is a common disease in orthopedics. Current clinical preparation techniques include autologous bone transplantation or the use of artificial bone, but the above technologies all have certain defects, such as limited material sources and low biological activity. It can be seen that there is still a lot of room for development in bone defect repair technology.

[0003] Bone tissue engineering is a research direction that has developed very rapidly in recent years. A series of materials in the form of hydrogels, scaffolds, etc. with bone repair functions have been developed in the hope of achieving good bone repair effects. However, scientists' current research focuses mostly on how to optimize the bone-promoting effect of materials. The raw materials used in tissue engineering materials are often natural biomacromolecules. Although they show good biocompatibility and degradability, they have major shortcomings in mechanical properties, which makes them prone to rupture and breakage during use, which greatly affects bone repair. The enhanced technologies in the field of traditional materials include chemical cross-linking and physical blending, but biomedical materials have higher requirements in terms of safety and functionality. Chemical cross-linking agents will bring higher biological toxicity, and the fillers introduced in the blending need to consider compatibility with the matrix. Therefore, how to develop a new strategy to achieve a significant improvement in the mechanical properties of bone tissue engineering materials is a major technical problem in this field.

[0004] In order to solve the above problems, the present invention designs a tangential double-enhanced gradient bone repair hydrogel material based on a concentric triangle ring structure. By introducing a concentric triangle ring composite structure, the tangential double enhancement of the hydrogel material is achieved. At the same time, through the gradual preparation process of the material, a decreasing HA concentration gradient from the inside to the outside is introduced, and angiogenic drugs are mixed in the outermost low-concentration HA gel matrix area to achieve early angiogenesis and full-cycle osteogenesis in bone repair. The above strategy provides a brand-new technology for bone repair. Summary of the invention

[0005] The purpose of the present invention is to provide a tangential double-reinforced gradient bone repair hydrogel material based on a concentric triangle ring structure and a preparation method thereof in order to solve the problems of poor mechanical strength and insignificant osteogenic activity of traditional bone repair hydrogels.

[0006] The present invention is implemented by the following technical solutions:

[0007] A method for preparing a tangential double-reinforced gradient bone repair hydrogel material based on a concentric triangle ring structure, comprising:

[0008] 1) Prepare a transparent casting mold: the mold consists of a base and a sleeve, the base is circular, the sleeve includes an outermost cylinder and a series of concentrically sleeved triangular cylinders arranged in the cylinder, the base is provided with a circular groove, a triangular groove is cut in the circular groove, a series of concentric triangular grooves are arranged in the triangular groove at equal intervals, all the cylinders are transparent plastic sleeves, which correspond to all the grooves one by one and can be disassembled or assembled;

[0009] 2) preparing AlgMA solutions compounded with different concentrations of HA, and adding angiogenic drugs to the solution with lower HA concentration to obtain a series of HA / AlgMA solutions;

[0010] 3) First, assemble the mold base and the innermost sleeve, and pour the prepared solution with the highest HA concentration into the innermost sleeve of the mold under light-proof conditions, and perform in-situ UV curing and freeze-demolding; then, assemble the sleeves on the base from the inside out, and synchronously circulate and pour the HA / AlgMA solution in the order of decreasing HA concentration, and perform curing and freeze-demolding until the outermost gel layer is prepared; finally, completely UV cure it, irradiate and sterilize it to obtain the desired bone repair hydrogel material.

[0011] Furthermore, in the step 1), 8 concentric triangular grooves and 1 outermost circular groove are provided on the base of the mold, the sleeve is composed of 8 detachable transparent concentric triangular cylindrical components and 1 outermost cylindrical component, and the sleeves and the grooves are combined one by one to form a total of nine layers of space from the inside to the outside in the outermost cylinder. There are 9 kinds of HA / AlgMA solutions, and the HA concentration is in the range of 1.5-10.5wt%, and the HA concentration in the HA / AlgMA solution corresponding to each layer decreases gradually by 1wt% from the inside to the outside.

[0012] Furthermore, the base has a diameter of 2-4 cm, the distance between the center of gravity of the innermost groove of the internal concentric triangular grooves and the vertex is 2-3 mm, the diameter of the outermost groove is 2-4 cm, and the middle grooves are evenly spaced, with a groove width of 0.3-0.5 mm and a depth of 2-5 mm; the detachable cylindrical component is made of PMMA or PET, with a thickness consistent with the corresponding groove width and a height of 10-20 cm.

[0013] Furthermore, the substitution degree of AlgMA in the HA / AlgMA solution is 30-60%, the concentration is 10-20wt%, a photoinitiator is added, the photoinitiator is one or more of LAP, Irgacure, photoinitiator 2959, etc., and the concentration is 0.25-0.5wt%; the particle size of HA is 100-300nm.

[0014] Furthermore, the angiogenic drug is one or more of deferoxamine, salvianolic acid B, astragaloside, ginsenoside, and paeoniflorin, etc., with a concentration of 0.5-2wt%, and is only added to the 2-3 AlgMA solutions with the lowest HA concentration;

[0015] Furthermore, the HA / AlgMA solution is prepared in a light-proof condition at a temperature of 60-70° C., with ultrasound-assisted dispersion and degassing, an ultrasound power of 180-200 W, and an ultrasound time of 15-40 min.

[0016] Furthermore, in step 3), the UV curing conditions are: UV wavelength of 405nm, power of 20-40W, irradiation time of 5-10s; frozen demoulding conditions are: freezing to -20--80℃, demoulding after the sample is melted; complete UV curing conditions: wavelength of 405nm, power of 20-30W, time of 10-15min. Compared with the prior art, the present invention has the following advantages:

[0017] 1) The present invention uses AlgMA, HA, angiogenic drugs and the like as raw materials, and combines blending, in-situ casting, UV curing, freeze demoulding and other combined processes to prepare a tangential double-enhanced gradient bone repair hydrogel material based on a concentric triangle ring structure. The above raw material selection and process combination are original to the present invention.

[0018] 2) The present invention achieves mechanical enhancement and optimization of osteogenic function of bone repair hydrogel materials by designing concentric triangle ring composite structures and spatial distribution of osteogenic and angiogenic drugs. The above strategy is the first of its kind in the present invention. In order to overcome the problem of unsatisfactory mechanical properties of traditional hydrogel materials, the present invention innovatively introduces a triangular structure inside the hydrogel. With the recognized stability of the triangular structure, it has the characteristics of being stable, firm and pressure-resistant. At the same time, through the setting of the concentric structure, a concentric triangle ring composite structure is formed inside the hydrogel, thereby enhancing the dual compression / bending strength of the hydrogel material in the tangential direction, ensuring that the material will not be broken or damaged due to pressure during use, thereby affecting the bone repair effect. On the other hand, under the premise of ensuring the mechanical properties of the material, its osteogenic bioactivity is further optimized: first, by designing the spatial distribution of the HA concentration gradient decreasing from the inside to the outside, a distribution trend of HA being low outside and high inside is formed, and secondly, angiogenic drugs are added to the outer low HA concentration layer. When the composite hydrogel material is used, the angiogenic drug in the outer layer is released first to promote angiogenesis in the bone defect area, while the internal HA gradually degrades to release calcium ions and phosphate ions to promote new bone formation. The angiogenesis occurs in the early stage of bone repair, and osteogenesis occurs in the entire bone repair process, which is in line with the natural bone repair time sequence. The mechanical enhancement and synergistic osteogenesis effects are achieved by the present invention in combination with specific raw material selection and unique material structure design, which is obviously innovative.

[0019] 3) In the present invention, a multi-layer transparent mold with a concentric triangle ring structure on the inner side is independently designed to achieve the preparation of the above-mentioned concentric triangle ring composite structure. The mold of the present invention is used in combination with cyclic casting of solutions with active materials of different concentrations, and further combined with in-situ UV curing and freezing demolding processes to successfully achieve the step-by-step construction of the hydrogel concentric triangle ring structure. It is precisely because of the unique structure and detachability of the mold of the present invention that the preparation requirements of the composite hydrogel material in the present invention can be met.

[0020] 4) The new composite bone repair material in the present invention has high biocompatibility, degradability, tangential dual compression / bending resistance, angiogenesis and coordinated osteogenesis, which is of great significance for bone defect repair. By selecting AlgMA, HA and angiogenesis drugs as raw materials, the material has excellent biodegradability and degradability, ensuring the basic requirements of its application; on the other hand, the unique concentric triangle ring composite structure and HA nanocomposite structure jointly enhance the mechanical properties of the hydrogel material, provide mechanical strength guarantee for the use of the material, and ensure its tangential dual compression / bending resistance; finally, in terms of functional performance, by constructing a concentric triangle ring composite structure in the hydrogel matrix with the characteristics of sequence and independence, a gradient trend of HA concentration is formed with high HA concentration inside and low HA outside, and at the same time, the HA concentration is low on the outside. The concentration of angiogenic drugs loaded in the gel layer allows the angiogenic drugs to occur in the early stage of the bone repair process when the hydrogel is used, providing abundant blood supply for bone repair and coordinating the new bone formation process in the later stage; while the osteogenesis process is a full cycle, and the low HA concentration in the outer layer is set because the early bone repair is less and the demand for calcium ions and phosphate ions is low. As new bones are gradually formed, the demand for calcium ions and phosphate ions gradually increases, and the high HA concentration inside can continuously supplement the above ion demand. It is the spatial distribution of the osteogenic active components designed above that enables the material to perfectly play its angiogenic and osteogenic functions. It is precisely because of the synergistic enhancement between all the above functions that the material can meet the complex needs of the bone defect repair process and ultimately obtain excellent bone tissue repair effects.

[0021] 5) In the present invention, by using a combination process of blending, step-by-step in-situ casting-UV curing-freezing demoulding, and complete UV curing lamp, in conjunction with the above-mentioned multi-layer transparent mold with a concentric triangle ring structure, the composite bone repair material we need can be successfully prepared. In the present invention, the material structure is carefully selected and organically used according to the needs of construction, which is a new application of traditional technology here and a combined innovative application, ensuring the smooth preparation of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the preparation process of tangential dual-reinforced gradient bone repair hydrogel material based on concentric triangular ring structure. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific examples. Figure 1 The figure shows a schematic diagram of the preparation process of the tangential double-reinforced gradient bone repair hydrogel material based on the concentric triangle ring structure of the present invention.

[0024] Comparative Example 1:

[0025] 1) Select AlgMA with a substitution degree of 60% and LAP as a photoinitiator, prepare a 10wt% AlgMA solution in a water bath at 60°C in a dark environment, wherein the LAP concentration is 0.25wt% and the solvent is PBS; add 5.5wt% HA (particle size is 100-300nm) to the above AlgMA solution; use an ultrasonic degassing instrument with a power of 200W for 20 minutes to obtain the desired solution.

[0026] 2) Pour the HA / AlgMA solution into a mold (i.e., a mold consisting of the outermost cylinder and the base) under light-proof conditions for in-situ UV curing (UV wavelength of 405 nm, power of 20 W, irradiation time of 10 min), freeze demolding, and irradiation sterilization to obtain the desired bone repair hydrogel material.

[0027] The extract of the above material was prepared and co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 days, and the CCK-8 result was about 93.6%; the material broke when bent for the second time, and the tangential compressive strength was about 126kPa; after being implanted into a rat bone defect model and raised for 28 days, heterotopic ossification occurred in some parts.

[0028] Embodiment 1:

[0029] 1) Prepare a transparent PMMA casting mold: the mold consists of a base with 8 concentric triangular grooves and an outermost circular groove, 8 detachable transparent concentric triangular cylindrical components and an outermost cylindrical component. The base has a circular appearance and is provided with a circular groove with a diameter of 3 cm, inscribed with a triangular groove, and a series of concentric triangular grooves are arranged at equal intervals inside to form a ring structure. The distance between the center of gravity of the innermost groove of the concentric triangular grooves and the vertex is 2 mm, the diameter of the outermost groove is 3 cm, and the middle grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 2 mm. All sleeves correspond to and are consistent with the interface structure of the grooves one by one, and are all transparent plastic sleeves with a thickness corresponding to the width of the above-mentioned grooves and a height of 10 cm, which are used for detachable combination with the base;

[0030] 2) AlgMA with a substitution degree of 60% and LAP as a photoinitiator were selected, and a 10wt% AlgMA solution was prepared in a light-proof condition and a 60°C water bath, wherein the LAP concentration was 0.25wt% and the solvent was PBS; different masses of HA (particle size of 100-300nm) were added to the above AlgMA solution, starting from 1.5wt% and increasing by 1wt%, and the angiogenic drug salvianolic acid B was added to the low-concentration HA solution (1.5wt% and 2.5wt%) at a concentration of 0.5wt%; an ultrasonic degassing device with a power of 200W was used for 20 minutes to obtain the desired solution.

[0031] 3) Assemble the mold base and the innermost sleeve, and pour the high-concentration HA solution (9.5 wt% HA) into the innermost sleeve of the mold under light-proof conditions for in-situ UV curing (UV wavelength of 405 nm, power of 20 W, irradiation time of 10 s) and freeze demolding (freeze to -20°C, demold after the sample melts); then assemble the sleeves on the base from the inside to the outside, and synchronously circulate and pour the HA / AlgMA solution in the order of decreasing HA concentration, and perform curing and freeze demolding until the outermost gel layer is prepared; finally, completely UV cure it (wavelength of 405 nm, power of 20 W, time of 10 min), and irradiate sterilize it to obtain the desired bone repair hydrogel material.

[0032] Compared with comparative example 1, this embodiment adds a concentric triangle ring composite structure to the hydrogel and adds angiogenic drugs to the outermost layer. The extract of the above material was prepared and co-cultured with BMSCs for 7 days. The CCK-8 result was about 91.2%; the material broke when it was bent for the 8th time, and the tangential compressive strength was about 269kPa; after implanting it into a rat bone defect model for 7 days, some new blood vessels appeared around the material, and new bone formation was good after 28 days.

[0033] Embodiment 2:

[0034] 1) Prepare a transparent PMMA casting mold: the mold consists of a base with 8 concentric triangular grooves and an outermost circular groove, 8 detachable transparent concentric triangular cylindrical components and an outermost cylindrical component. The base has a circular appearance and is provided with a circular groove with a diameter of 3 cm, inscribed with a triangular groove, and a series of concentric triangular grooves are arranged at equal intervals inside to form a ring structure. The distance between the center of gravity of the innermost groove of the concentric triangular grooves and the vertex is 2 mm, the diameter of the outermost groove is 3 cm, and the middle grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 2 mm; all sleeves correspond to and are consistent with the groove interface structure, and are transparent plastic sleeves with a thickness corresponding to the above groove width and a height of 10 cm, which are used for detachable combination with the base;

[0035] 2) Select AlgMA with a substitution degree of 60% and LAP as a photoinitiator, prepare a 10wt% AlgMA solution in a light-proof condition and a 60°C water bath, wherein the LAP concentration is 0.25wt% and the solvent is PBS; add different masses of HA (particle size of 100-300nm) to the above AlgMA solution, increasing by 1wt% from 1.5wt% to 9.5wt%; use an ultrasonic degassing instrument with a power of 200W for 20 minutes to obtain the desired solution.

[0036] 3) Assemble the mold base and the innermost sleeve, and pour the high-concentration HA solution (9.5 wt% HA) into the innermost sleeve of the mold under light-proof conditions for in-situ UV curing (UV wavelength of 405 nm, power of 20 W, irradiation time of 10 s) and freeze demolding (freeze to -20°C, demold after the sample melts); then assemble the sleeves on the base from the inside to the outside, and synchronously circulate and pour the HA / AlgMA solution in the order of decreasing HA concentration, and perform curing and freeze demolding until the outermost gel layer is prepared; finally, completely UV cure it (wavelength of 405 nm, power of 20 W, time of 10 min), and irradiate sterilize it to obtain the desired bone repair hydrogel material.

[0037] Compared with Example 1, the addition of angiogenic drugs was reduced in this example. The extract of the above material was prepared and co-cultured with BMSCs for 7 days, and the CCK-8 result was about 91.6%; the material broke when it was bent for the 8th time, and the tangential compressive strength was about 262 kPa; after implanting it into a rat bone defect model and feeding it for 28 days, the new bone formation was good, but the volume of the new bone formation was reduced by about 15% compared with the example.

[0038] Embodiment 3:

[0039] 1) Prepare a transparent PMMA casting mold: the mold consists of a base with 8 concentric triangular grooves and an outermost circular groove, 8 detachable transparent concentric triangular cylindrical components and an outermost cylindrical component. The base has a circular appearance and is provided with a circular groove with a diameter of 3 cm, inscribed with a triangular groove, and a series of concentric triangular grooves are arranged at equal intervals inside to form a ring structure. The distance between the center of gravity of the innermost groove of the concentric triangular grooves and the vertex is 2 mm, the diameter of the outermost groove is 3 cm, and the middle grooves are evenly spaced, with a groove width of 0.3 mm and a depth of 2 mm; all sleeves correspond to and are consistent with the groove interface structure, and are transparent plastic sleeves with a thickness corresponding to the above groove width and a height of 10 cm, which are used for detachable combination with the base;

[0040] 2) Select AlgMA with a substitution degree of 60% and LAP as a photoinitiator, prepare a 10wt% AlgMA solution in a light-proof condition and a 60°C water bath, wherein the LAP concentration is 0.25wt%, and the solvent is PBS; add 5wt% HA (particle size is 100-300nm) to the above AlgMA solution; at the same time, prepare a HA / AlgMA solution added with angiogenic drug salvianolic acid B, and add it at a concentration of 0.5wt%; use an ultrasonic degassing device with a power of 200W for 20 minutes to obtain the desired solution.

[0041] 3) Assemble the mold base and the innermost sleeve, pour the HA / AlgMA solution into the innermost sleeve of the mold under light-proof conditions for in-situ UV curing (UV wavelength of 405 nm, power of 20 W, irradiation time of 10 s) and freeze demolding (freeze to -20°C, demold after the sample melts); then assemble the sleeves on the base from the inside out, repeat the above casting-curing-freezing demolding process, and the outermost two layers are cast with HA / AlgMA solution added with angiogenic drugs; finally, completely UV cure (wavelength of 405 nm, power of 20 W, time of 10 min) and irradiation sterilization to obtain the desired bone repair hydrogel material.

[0042] Compared with Example 1, the HA concentration gradient design was removed in this example. The extract of the above material was prepared and co-cultured with BMSCs for 7 days, and the CCK-8 result was about 94.3%; the material broke when it was bent for the 10th time, and the tangential compressive strength was about 244 kPa; after implanting it into a rat bone defect model and feeding it for 7 days, some new blood vessels appeared around the material, and some ectopic osteogenesis occurred after 28 days.

Claims

1. A method for preparing a tangential double-enhanced gradient bone repair hydrogel material based on a concentric triangle ring structure, characterized in that: The following steps are involved: 1) Prepare a transparent casting mold: The mold consists of a base and a sleeve. The base is circular. The sleeve includes an outermost cylinder and a series of concentrically sleeved triangular cylinders arranged in the cylinder. The base is provided with a circular groove, a triangular groove is cut in the circular groove, and a series of concentric triangular grooves are arranged in the triangular groove at equal intervals. All the cylinders are transparent plastic sleeves, which correspond to all the grooves one by one and can be disassembled or assembled; 2) preparing methacryloyl sodium alginate (AlgMA) solutions compounded with different concentrations of hydroxyapatite (HA), and adding angiogenic drugs to the solution with lower HA concentration to obtain a series of HA / AlgMA solutions; 3) First, assemble the mold base and the innermost sleeve, and pour the prepared solution with the highest HA concentration into the innermost sleeve of the mold under light-proof conditions, and perform in-situ UV curing and freeze-demolding; then, assemble the sleeves on the base from the inside out, and synchronously circulate and pour the HA / AlgMA solution in the order of decreasing HA concentration, and perform curing and freeze-demolding until the outermost gel layer is prepared; finally, completely UV cure it, irradiate and sterilize it to obtain the desired bone repair hydrogel material.

2. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 1, characterized in that: In step 1), the base of the mold is provided with 8 concentric triangular grooves and 1 outermost circular groove, the sleeve is composed of 8 detachable transparent concentric triangular cylindrical components and 1 outermost cylindrical component, and the sleeves and the grooves are combined one by one to form a total of nine layers of space from the inside to the outside in the outermost cylinder. There are 9 kinds of HA / AlgMA solutions, and the HA concentration is in the range of 1.5-10.5wt%, and the HA concentration in the HA / AlgMA solution corresponding to each layer decreases gradually by 1wt% from the inside to the outside.

3. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 2, characterized in that: The base has a diameter of 2-4 cm, the distance from the center of gravity of the innermost groove of the internal concentric triangular grooves to the vertex is 2-3 mm, the diameter of the outermost groove is 2-4 cm, and the middle grooves are evenly spaced, with a groove width of 0.3-0.5 mm and a depth of 2-5 mm; the detachable cylindrical component is made of PMMA or PET, with a thickness consistent with the corresponding groove width and a height of 10-20 cm.

4. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 1, characterized in that: The substitution degree of AlgMA in the HA / AlgMA solution is 30-60%, the concentration is 10-20wt%, a photoinitiator is added, the photoinitiator is one or more of LAP, Irgacure, and photoinitiator 2959, and the concentration is 0.25-0.5wt%; the particle size of HA is 100-300nm.

5. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 1, characterized in that: The angiogenic drug is one or more of deferoxamine, salvianolic acid B, astragaloside, ginsenoside and paeoniflorin, with a concentration of 0.5-2wt%, and is only added to 2-3 HA / AlgMA solutions with the lowest HA concentration.

6. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 1, characterized in that: The preparation conditions of HA / AlgMA solution are light-proof conditions, temperature of 60-70°C, ultrasonic-assisted dispersion and degassing, ultrasonic power of 180-200W, and ultrasonic time of 15-40min.

7. The method for preparing the tangential double-enhanced gradient bone repair hydrogel material based on the concentric triangle ring structure according to claim 1, characterized in that: In step 3), the UV curing conditions are: UV wavelength of 405nm, power of 20-40W, and irradiation time of 5-10s; the freezing demoulding conditions are: freezing to -20--80°C, and demoulding after the sample melts; the complete UV curing conditions are: wavelength of 405nm, power of 20-30W, and time of 10-15min.

8. A tangential double-reinforced gradient bone repair hydrogel material based on a concentric triangle ring structure, characterized in that: The method is prepared according to any one of claims 1 to 7.